2014
DOI: 10.1016/j.rmed.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multidimensional COPD-related subjective fatigue following a Pulmonary Rehabilitation programme

Abstract: Introduction: Subjective fatigue has been recognised as an important, multi-component symptom in COPD. Pulmonary Rehabilitation (PR) improves fatigue component of the Chronic Respiratory Questionnaire, a quality of life (QoL) measure. However, it is not clear if all fatigue dimensions are affected equally. This study aims to evaluate changes in subjective multidimensional fatigue among people with COPD who participated in PR. Methods: Thirty seven stable COPD patients were recruited; 23 patients (15 male) mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
(47 reference statements)
1
19
1
Order By: Relevance
“…The depression score was not improved by PR in the present study nor in our previous cohort study with a larger number of patients . Most of the previous studies showed that PR improved depression and anxiety scores, although some studies showed the depression score did not change after PR . This discrepancy might be explained by the differences in the PR programs.…”
Section: Discussioncontrasting
confidence: 89%
“…The depression score was not improved by PR in the present study nor in our previous cohort study with a larger number of patients . Most of the previous studies showed that PR improved depression and anxiety scores, although some studies showed the depression score did not change after PR . This discrepancy might be explained by the differences in the PR programs.…”
Section: Discussioncontrasting
confidence: 89%
“…It is a known symptom of advanced lung diseases that impacts quality of life and psychological health [2]. There is a general impression that features of fatigue manifest as underlying depression [3] however, each differ and may represent different aspects of underlying psychological impairment.…”
Section: Introductionmentioning
confidence: 99%
“…These patients regularly undergo pulmonary rehabilitation as part of their therapy [2,6]. Rational for using pulmonary rehabilitation as an adjuvant to pharmacotherapy is well established [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary rehabilitation including exercise training has been shown to increase exercise capacity 134 but the effect of pulmonary rehabilitation on physical activity seems to be small 135 . A recent study showed that pulmonary rehabilitation improved different dimensions of fatigue 136 . However, the impact of fatigue on motivation and mental functions remained unchanged, thus suggesting that fatigue might still influence the motivation to engage in PA after pulmonary rehabilitation.…”
Section: Factors Associated With Low Physical Activitymentioning
confidence: 99%